From Iwe Irohin to saharareporters.com: hardcoding citizen journalism in Nigeria - Olaniyan, Akintola (My University, 2022)
Nigeria’s fourth republic was supposed to deliver much more than the previous attempts at democratic rule. After decades of military rule, during which the media had been a rallying point for pro-democracy activism, the return to elective civilian rule in 1999 was supposed to launch Nigeria into a new order of democracy and development. The media, active in its normative role as watchdogs during the campaign against military rule, was supposed to be pivotal in the new order. Particularly since the 1999 Constitution and new laws like the Freedom of Information Act (FOI) (2011) appear to remove some of the obstacles to their operations. However, performance of the media post-1999 has drawn criticism as Nigeria moved from one electoral cycle to another without evidence of impact on people’s lives. This criticism has largely centred on the media’s failure to hold politicians to account. New media platforms in the meantime are disrupting the media industry in Nigeria and appear to be taking the lead in performing the normative watchdog role by holding politicians to account; as an increasing number of people adopt these new channels for political communication and citizen journalism. While they appear to allow many more people into the communicative discourse, the significance and impact of new media platforms on democratic processes are still unclear. This study is a critical assessment of the media’s performance post-1999 using political economy and the public sphere as the theoretical lenses. The study interrogates the emergence of new, digital-born news platforms into the Nigerian media post-1999. The study critically examines the contestations around the operations of news platforms like Sahara Reporters, Premium Times and The Cable. This includes studying their claim to popularity and their perception as alternatives to the traditional newspapers like The Guardian, The Punch and Nigerian Tribune. Some of those contestations centre around the claims that the new media platforms are counter-hegemonic because they accommodate more ordinary viewpoints. This is in contrast to the traditional newspapers which are considered hegemonic because they are less accommodating of ordinary viewpoints. The study draws on three data sets: first, twelve purposive qualitative interviews with Nigerian editors and publishers at The Guardian, The Punch, Nigerian Tribune, Sahara Reporters, Premium Times and The Cable; second, an online survey of Nigerian media users conducted between February and July 2020; and third, content analysis of 41 selected newspaper stories. The study finds that new media may have democratised the communicative environment by allowing many ordinary Nigerians access to media that was impossible with traditional newspapers. However, there is still an elite domination of overall communication online. The study also finds that, while the likes of Sahara Reporters, Premium Times and The Cable stand in contrast to The Guardian, The Punch and Nigerian Tribune, most of the differences relate to perception rather than any real difference in the quality of access given to media users. The study finds that the ecosystem of new media allows for more ordinary participation in the communicative process. Furthermore, that some features can be copied by the more traditional newspapers to improve the overall performance of the media and its impact on the democratic process.
A thesis submitted in fulfilment of the requirements for the Doctor of Philosophy in Media Studies to the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, 2022